Meanings attributed to the perception of to be-ostomized-in-the-world (Estima – Brazilian Journal of Enterostomal Therapy, 2019)
Objective: To understand the meanings of the experience of to be-ostomized-in-the-world through Merleau-Ponty phenomenology. Method: Descriptive study with a qualitative approach, in the merleau-ponty phenomenological perspective, conducted through interviews with ten people with intestinal stomas assisted by the Association of Ostomized of the State of Ceara. The IRaMuTeQ software was used. Similarity analysis and word cloud were adopted. Results: The words ‘person’, ‘much’, ‘how’, ‘see’ and ‘bag’ was identified by discourse analysis, which gave rise to ‘say’, as central nuclei. The ‘person’, as be-ostomized-in-the-world, perceives itself as’ being-sick ‘that’ reluctantly ‘senses-motor sensations (feces and odors) that cause’ repulsiveness’, marked by the presence of the ‘ (stoma and bag). The words most often in the cloud were ‘bag’, ‘life’, ‘God’, ‘people’ and ‘surgery’. The collector bag evidences ‘abnormality’ and bodily imperfection. Conclusion: The perception of be-ostomized-in-the-world is marked by the presence of the collector bag of stoma, being perceived as new element of its body.
Keywords: Stoma; Surgical stomas; Perception; Adaptation; Stomatherapy